The Influence Of Service Quality On Patient Satisfaction At The Pupuk Kaltim Prima Sangatta Hospital - Harmawati, Harmawati; M. Ramdan, Iwan; Sedionoto, Blego (Mulawarman International Conference on Tropical Public Health, 2025)
Background: This research highlights the importance of the quality of health services in hospitals to increase patient satisfaction. The research gap lies in the lack of understanding of the influence of each quality dimension on patient satisfaction, as well as the need to identify areas that need improvement to meet patient expectations. Objective: The objective is to analyze the impact of service quality dimensions and aims to identify which specific dimensions most significantly influence patient satisfaction and to provide insights that can help improve the quality of healthcare services offered by the hospital. Research Methods/ Implementation Methods : This study is a quantitative approach using a descriptive-analytical design with a cross-sectional survey. The study identifies independent variables (empathy, tangibility, assurance, reliability, and responsiveness) and a dependent variable (patient satisfaction). With a sample size of 85 respondents selected through proportional stratified random sampling, and using questionnaire, and statistical analyses, including univariate, bivariate, and multivariate tests. Results : The study's statistical tests demonstrated that all five quality dimensions significantly impact patient satisfaction simultaneously. The significance value of the F test = 0.000, which is below the threshold of 0.05. The calculated F value is 30.685, which is greater than the F table value of 2.33. Statistical tests showed the dimensions of Tangible/physical evidence (p = 0.000<0.05), assurance (p = 0.000<0.05), and responsiveness (p = 0.007<0.05) impacted substantially. Conclusion/Lesson Learned : The findings suggest that enhancing these service quality dimensions can lead to improved patient satisfaction, highlighting the importance of quality healthcare services in fostering patient trust and contentment.